Prevalence of Direct and Emergent Schema and Change after Play - MARTIN, Kit; HORN, Michael; Wilensky, Uri (Informatics in education, 2019)
This paper describes visitor interaction with an interactive tabletop game on the topic of evolutionary adaptations of social insects that we designed in collaboration with a large American museum. We observed visitors playing the game and talked to them about the experience. The game explores the emergent phenomena of ant behavior. Research has shown that such emergent behavior is difficult for people to understand, and that there are different emergent schemas that work best for understanding these phenomena. We tested the visitors pre- and post-gameplay and counted the prevalence of visitors expressing direct and emergent schemas of complex processes. We then considered four hypotheses measuring changes between these schemas and found that two groups shifted their schemas. To better understand this change we provide a qualitative overview of the visitors' interactions. Our exhibit, called Ant Adaptation, takes the form of an agent-based modeling game that integrates complex system learning with gameplay. We video recorded 38 groups (114 participants) playing the game and conducted pre- and post-gameplay interviews. We coded the groups that contained children for this analysis: 9 groups (27 participants). Our results show that visitors held both emergent and direct schemas before and after play, and three people changed from direct schemas before play to emergent schemas after play. We then examine the process of how one of these groups shifted their schemas.